Investigation of solvability condition for sixth-order boundary value problem - Akram Hassan Mahmood; Alaa Ahmed Mohamed (مجلة التربية والعلم, 2012)
Abstract This paper is concerned with the solvability condition for nonhomogenous linear boundary value problem for sixth-order ordinary differential equation. Throughout this study, we observed that, when the homogenous problem have nontrivial solution,then the nonhomogenous boundary value problem have a solution in case of nonhomogenous term that satisfied the solvability condition. We justified our results through the given example. Keywords :Sixth-order boundary value problem, self-adjoint problem.